Effect of Vitamin D Administration on Glycemic Control in Patients with Type II Diabetes Mellitus and Vitamin D Deficiency - Mosalanejad, Shima; Shahrzad, Mohammad Karim; Pishgahi, Mehdi; Karimi Toudeshki, Kimia; Ghanefard, Shirin; Ebadi, Seyed Alireza (Archives of Men’s Health, 2021)
Introduction: The prevalence of diabetes mellitus (DM) and its morbidity and mortality are prominent all over the world. Observational data suggest that vitamin D deficiency is associated with insulin resistance. In this study, we aimed to assess this association. Methods: This study was a clinical trial consisting of 42 patients with type 2 DM who had vitamin D deficiency. The patients underwent vitamin D replacement with vitamin D pearls (50,000 iu) weekly for 10 weeks. The level of low-density lipoprotein (LDL), high-density lipoprotein (HDL), cholesterol (Chol), triglycerides (TG), hemoglobin A1c (HbA1C), 2 hour post prandial (2HPP), fasting blood sugar (FBS), body mass index (BMI), blood pressure (BP), and 25oHVitD3 were measured before and after the treatment in all patients. Data were analyzed with paired t test. Results: 100% of patients reached acceptable vitamin D level (above 30 mg/dl). No toxicity was reported. Changes in FBS, 2Hpp, HbA1C, Chol, SBP were significant and there was no significant change in LDL, HDL, and DBP. Conclusion: Screening for vitamin D deficiency and its replacement may have a beneficial effect on type 2 DM management and its associated risk factors. More studies with larger sample size and use of placebo are recommended.